Analisis Paving Block berdasarkan Sifat Tampak dan Reduksi Limbah Plastik Multilayer, Limbah Keramik Sanitary, dan Limbah Karet Alas Sepatu - fatma nurkhaerani; Gina Lova Sari; Fransisca Debora; Eka Oktariyanto Nugroho; Zalfa Dziaul Hassalum; Ayya Sophia Ahmad (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), 2024)
Multilayer plastic waste, sanitary ceramics and rubber have potential as paving block mixtures. Multilayer plastic waste is difficult to decompose and recycle, resulting in minimal management. In addition to multilayer plastic waste, rubber waste is also hard to decompose because it is a non-organic waste resistant to water, soil, and chemical compounds. Ceramic waste can be used as a mix for paving blocks due to its durability and strength, and it helps reduce the volume of waste being disposed of. This research aims to see the suitability of the visible properties of paving blocks from these three wastes with SNI 03-0691-1996 concerning Concrete Bricks (Paving Blocks) and the amount of waste reduction potential. Making paving blocks uses 8 (eight) compositions, namely Ceramic Waste (LKK): Multilayer Plastic Waste (LPM) at 20%:80%, 30%:70%, 40%:60% and 0%:100%. Then Ceramic Waste (LKK): Multilayer Plastic Waste (LPM): and Rubber Waste (LKT) at 20%:60%:20%, 30%:50%:20%, 40%:40%:20%, and 50%:30%:20%. The visible properties of paving blocks that comply with SNI 03-0691-1996 are only found in some samples. Non-compliance with SNI can be caused by several things, including varying composition amounts, mixing materials (homogenization) and paving block printing. Based on the results of making paving blocks with 8 (eight) different compositions, there are 3 (three) compositions whose properties appear to be by SNI 03-0691-1996, namely at a composition of 20% LKK: 80% LPM, 100% LPM, and 20 % LKT: 60% LPM: 20% LKK. The amount of waste reduction from these three wastes ranges from 167.6 kg to 768 kg. Keywords: waste, plastic, ceramic, rubber, paving block.